Overweight and obesity among children and adolescents in Bangladesh: a systematic review and meta-analysis - Biswas, Tuhin; Islam, Anwar; Islam, Md Serajul; Pervin, Sonia; Rawal, Lal Bahadur (© 2017 Elsevier B.V., 2018)
This review was published in the Public Health [© 2016 The Royal Society for Public Health] and the definitive version is available at: http://doi.org/10.1016/j.puhe.2016.10.010 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S0033350616303122?via%3Dihub